Predictors for a positive start from Footprints in Time - Skelton, F; Walter, Maggie (My University, 2015)
More than 1700 families began the Footprints in Time journey back in 2008 when the LSIC study children were babies and four year olds. Each year Aboriginal and Torres Strait Islander interviewers return to families to talk with parents and carers and the children themselves, so now in 2015, we have six waves of data collected. In this presentation we identify factors that support a positive start for our LSIC kids, focussing on the contribution of early years to the wellbeing and learning outcomes of the children who are now in primary school. Our analysis details positive start predictors associated with children’s cultural and social circumstances and life experiences as well as those associated with children and their family’s early years’ engagement with educational institutions and programs. Our results lead us to ask: is a positive start all about good relationships?
Keywords: Children -- Indigenous; Culture -- Indigenous; Relationships; Culture and language; Families and relationships; Children; Culture; Relationships; Indigenous; Culture and identity; Families and relationships; Culture, identity and language